Pengaruh Perbedaan Pendekatan Pembelajaran dan Persepsi Kinestetik Terhadap Hasil Tembakan Lay Up Bola Basket - Prasetia, Putra (Jurnal Simki Postgraduate, 2023)
This study used an experimental method with a 2 x 2 factorial design. The population in this study were class X students of SMA Negeri 8 Kota Kediri in the 2016-2017 academic year, totaling 170 students. the sampling technique used was purposive sampling. The sample to be used in this research is 15 students. Data collection techniques using kinesthetic perception were measured by the Vertical Linear Space Test and the lay-up data collection was measured by the Wincousin Bounce and Shoot test. The data analysis technique used is a two-way ANOVA. Research results: 1) Based on two-way anava analysis, Sig. = 0.000 <0.05 or Fcount value (17.298) > Ftable (4.085), this means that there is a difference in the effect of dense practice and distributed practice on the results of basketball lay-up shots; 2) Based on the two-way anava analysis, the value of Sig. = 0.002 <0.05 or Fcount (11.048) > Ftable (4.085) this means that there are differences in the results of basketball lay-up shots between male students who have high and low kinesthetic perceptions; and 3) Based on the two-way anava analysis, Sig. = 0.000 <0.05 or Fcount value (25.637) > Ftable (4.113) this means that there is an interaction effect between the learning approach and kinesthetic perception on the results of the basketball lay-up shot. The conclusions of this study are (1) There is a significant difference in the effect of learning approaches with dense and distributed practice on the results of basketball lay-up shots. The effect of a distributed practice learning approach is better than solid practice on the results of basketball lay-up shots; (2) There is a significant difference in the effect of high kinesthetic perception and low kinesthetic perception on the result of a basketball lay-up shot. The results of a basketball lay-up shot on students who have high kinesthetic perception are better than those who have low kinesthetic perception; 3) There is a significant interaction between the learning approach and kinesthetic perception of the result of a basketball lay-up shot.